Firstsite : art spaces - Merrick, Jay. ([S.l.] : Scala Publishers, 2012)
The latest book in Scala's Art Spaces series examines the design and delivery of the innovative Firstsite building.
Keywords: Art museums--Design and construction; England--Colchester; Museum architecture